2019
DOI: 10.1016/j.actpsy.2019.102888
|View full text |Cite
|
Sign up to set email alerts
|

Mental representations of partner task cause interference in picture naming

Abstract: Interference in picture naming occurs from representing a partner's preparations to speak (Gambi, van de Cavey, & Pickering, 2015). We tested the origins of this interference using a simple non-communicative joint naming task based on Gambi et al. (2015), where response latencies indexed interference from partner task and partner speech content, and eye fixations to partner objects indexed overt attention. Experiment 1 contrasted a partnerpresent condition with a control partner-absent condition to establish t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(29 citation statements)
references
References 22 publications
7
20
0
Order By: Relevance
“…Interestingly, participants tended to look more often at their partner's picture when they knew they were naming rather than categorizing, and also when the partner's picture was different to their own, but overall there were very few looks to partner's pictures, suggesting that speakers did not regularly engage in detailed representation of their partner's utterances. In sum, the findings of Gambi et al (2015) and Brehm et al (2019) are consistent with other work (Baus et al, 2014;Demiral et al, 2016;Kuhlen & Abdel Rahman, 2017;Hoedemaker et al, 2017) in showing that speakers represent their partners' act of production in a similar way to how they represent their own act of production. However, they also suggest that the content of others' utterances (i.e., what they are saying) may not be represented: there was only inconsistent evidence of increased interference when producing a different utterance from one's partner, compared to producing the same utterance.…”
Section: Representing Another's Utterances While Simultaneously Prepa...supporting
confidence: 89%
See 2 more Smart Citations
“…Interestingly, participants tended to look more often at their partner's picture when they knew they were naming rather than categorizing, and also when the partner's picture was different to their own, but overall there were very few looks to partner's pictures, suggesting that speakers did not regularly engage in detailed representation of their partner's utterances. In sum, the findings of Gambi et al (2015) and Brehm et al (2019) are consistent with other work (Baus et al, 2014;Demiral et al, 2016;Kuhlen & Abdel Rahman, 2017;Hoedemaker et al, 2017) in showing that speakers represent their partners' act of production in a similar way to how they represent their own act of production. However, they also suggest that the content of others' utterances (i.e., what they are saying) may not be represented: there was only inconsistent evidence of increased interference when producing a different utterance from one's partner, compared to producing the same utterance.…”
Section: Representing Another's Utterances While Simultaneously Prepa...supporting
confidence: 89%
“…However, the effect was not significant (t = -1.12) when we instead discarded these data points (1.14%), suggesting that the effect may have been driven by a subset of very long durations. In support of this, when we ran a Bayesian ex-Gaussian distributional analysis (Bürkner, 2016), we found a small effect of Form on the mean of The nature of the representations speakers formed of their partner's imagined utterances was also similar in this task to simpler production tasks (Gambi et al, 2015;Brehm et al, 2019): There was no evidence that speakers took longer to begin their utterances when they believed their partner was preparing to produce an utterance in a different, compared to the same, voice. However, when we analysed utterance durations, we unexpectedly found that speakers spent more time producing their utterances when the partner produced a different utterance than when they produced the same utterance.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…If speakers had represented the second speaker’s action to the degree that they pursued lexical access, the authors reasoned, naming should have slowed down when speakers believed partners to be naming different pictures compared to naming the same pictures. These conclusions were corroborated by a recent study (Brehm, Taschenberger, & Meyer, 2019), which applied a similar task setting. In this study participants’ naming latencies were also affected by the partner’s task (yet, interestingly, in the opposite direction found in Gambi et al, 2015).…”
supporting
confidence: 81%
“…However, there is a growing number of studies employing joint picture naming tasks that also report only limited, or no, representation of the partner's naming response (Brehm et al, 2019;Gambi, Van de Cavey, & Pickering, 2015;Hoedemaker & Meyer, 2019). These studies come to the conclusion that speakers may represent their partner's naming response, but not necessarily to the degree that they seek lexical access for the pictures the partner names.…”
Section: Discussionmentioning
confidence: 99%